1988
DOI: 10.1159/000199658
|View full text |Cite
|
Sign up to set email alerts
|

Large Bowel Cancer Risk in Cholelithiasis and after Cholecystectomy

Abstract: To assess the large bowel cancer risk in cholelithiasis (CL) and after cholecystectomy (CE), the results of 11,828 autopsies were analyzed. 1,705 cases with CL and 380 with CE could be identified. Randomly selected cases matched for sex and age were used as controls. In CL and CE 61 cancers were observed compared with 53 in controls, the relative risk (RR) being 1.2. The risk ratio for the subgroups (CL, CE) was also 1.2. In contrast to women, there was a positive association (RR 1.7) between cancer and CL in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…Some epidemiological studies (Table 3) [6,10,34,40,41,75,76] have implicated surgical cholecystectomy as a contributor to an increased incidence of colon cancerparticularly in the right colon in females. Some experimental studies also purport to show such a relation [47,49,56,57,66,77,78].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some epidemiological studies (Table 3) [6,10,34,40,41,75,76] have implicated surgical cholecystectomy as a contributor to an increased incidence of colon cancerparticularly in the right colon in females. Some experimental studies also purport to show such a relation [47,49,56,57,66,77,78].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a significant percentage of patients continue to have abdominal symptoms months to years following cholecystectomy (Table 2) [7,8,24,36,60,68]. Furthermore, there are reports suggesting that cholecystectomy may increase the risk of colon cancer (Table 3) [1,2,6,10,20,34,40,41,47,49,56,57,66,[74][75][76][77][78].…”
mentioning
confidence: 99%
“…The conclusions of this study were that gallstones, and not the cholecystectomy itself, were important in the development of colorectal carcinoma. [12,15,18,23,29,76]. Some incorporate long follow-up times in the study design such as over 10 years [2,64].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of gall stone patients have been reported [23][24][25][26][27][28][29][30][31][32] ; most showed a positive association with cancer of the colon, with relative risks of 1.2-2.4. In the studies that showed an effect and provided data on risk by anatomical sub-site, the risk was generally greater for cancer of the proximal colon than for other parts of the colon and rectum [28][29][30][31][32] .…”
Section: Issn 2331-2726 E-issn 2331-2734mentioning
confidence: 99%
“…In the studies that showed an effect and provided data on risk by anatomical sub-site, the risk was generally greater for cancer of the proximal colon than for other parts of the colon and rectum [28][29][30][31][32] .…”
Section: Issn 2331-2726 E-issn 2331-2734mentioning
confidence: 99%